REVIEW ARTICLE : AROMATERAPI SEBAGAI TERAPI STRES DAN GANGGUAN KECEMASAN - Adinda Khansa Sundara; Bintang Larasati; Dewi Sheyka Meli; Dheandra Mariska Wibowo; Fitri Nurulliza Utami; Silky Maulina; Yuliana Latifah; Neni Sri Gunarti (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Stress and anxiety are one of the mental disorders that are still a problem in Indonesia. Stress and anxiety can be experienced by anyone that can be caused by certain conditions. Aromatherapy treatment is an alternative to reduce stress and anxiety levels. Aromatherapy is a therapy that uses essential oils as the main agent. The purpose of this study was to determine which essential oils can reduce stress and anxiety levels in various patient conditions. The method used in this research was a literature review study consist of 16 article from online search site . The results of the study showed that essential oils from lavender (Lavandula angustifolia), bergamot orange (Citrus bergamia Risso et Poiteau), lemon (Citrus limon (L.) Burm. F), peppermint (Mentha piperita L.), chamomile (Matricaria Chamomilla L), ylang flower (Cananga Odorata (ylang-ylang)), lemongrass (Cymbopogon ciratus (DC.), bitter orange (Citrus aurantium (L.), and rosemary (Rosemarinus officinalis L.) can be used to reduce stress and anxiety levels caused by certain conditions.